Application of Benson's Relaxation Therapy to Reducing Anxiety in Patients Hypertension: Case Study - Novita, Merli; Emilia, Ni Luh; Sabarulin, Sabarulin; Assa, Anggri Alfira Yunita; Purwanza, Sena Wahyu (STIKES Adi Husada, 2023)
Hypertension or high blood pressure is a condition characterized by increased blood pressure on the walls of the arteries. Once the person worries about the emergence of a new problem in hypertension will cause emotional mental disorders or feelings that we often encounter, one of which is anxiety. Pharmacological and non-pharmacological methods can overcome anxiety problems experienced by patients; one of them is the Benson therapy technique. Benson relaxation will make a person feel relaxed. Based on this, the study aimed to determine the effect of applying Benson relaxation therapy procedures in reducing anxiety in patients who have hypertension. This research used a descriptive case study design. The research subject was 1 person, and data were collected through interviews, observation, and documentation studies which were carried out 2 times a day for 7 days. The result obtained before giving therapy was that the client experienced anxiety with a HARS value of 24 (moderate anxiety) and the blood pressure was 160/80 mmHg, after being given Benson relaxation technique therapy 2 times a day in 7 days was that the HARS value became 16 (mild anxiety) and the blood pressure becomes 140/90 mmHg which means there was a decrease in anxiety levels. It is hoped that further researchers can consider the length of administration and for health workers to use this Benson relaxation therapy as an alternative in providing nursing care to patients with anxiety.